Antioxidative, Antihypertensive and Antidiabetic Activities of Cocoa Autolysates Using in Vitro Models - Hosseinpoursarmadi, Bahareh (2011)
This study investigated antioxidant, antihypertensive and antidiabetic activities of cocoa (Theobroma cacao L.) autolysates using in vitro methods. After removal of cocoa fat, alkaloids and polyphenols, the remaining proteinous powder was prepared and autolyzed at pH 3.5 and 5.2. Antioxidant capacity was assayed using two different methods namely, ferric reducing/antioxidant potential (FRAP) and β-carotene bleaching assays. The antihypertensive potential of cocoa autolysates was measured using angiotensin converting enzyme (ACE) inhibitory effects. α-Amylase, α-glucosidase inhibition and insulinotropic activities of autolysates were measured to assess potential antidiabetic activities. Qualitative and quantitative tests were applied to assure that the results from the aforementioned assays were not due to the polyphenols of cocoa autolysates. In addition, amino acid compositions of autolysates and their protein content were determined by HPLC following Pico-Tag and Kjeldah methods, respectively. At similar concentrations (10 mg/ml), autolysates of UIT 1 produced at pH 3.5 exhibited the highest reducing power (723 μM) and ACE inhibition activity (75%). However, autolysates of PBC 140 generated at pH 5.2 showed the highest antioxidant activity (54%) based on β-carotene bleaching assay. In the case of antihyperglycemic properties, autolysate of UIT produced at pH 3.5 had the highest ability (68%) to inhibit α-amylase. No α-glucosidase inhibition activity was observed from autolysates. Autolysates produced under pH 3.5 caused the highest amount of insulin secretion in the concentration of 0.62 mg/ml, although the difference was not significant. The reducing power, antioxidant, ACE inhibitory and α-amylase inhibitory activities of all autolysates as well as insulinotropic properties of autolysates produced at pH 5.2 was enhanced by increasing their concentration. However, autolysates produced at pH 3.5 showed maximum potential insulinotropic activity at 0.62 mg/ml and then decreased. No polyphenols could be detected from cocoa autolysates. Based on amino acids composition, slight differences were detected between autolysates, and as it was found, they were rich in hydrophobic amino acids. There was a significant (P<0.01) and high correlation between protein content and reducing power (r2=0.827), ability to suppress β-carotene bleaching (r2=0.762), α-amylase inhibition (r2=0.766) as well as insulinotropic effect, at pH 5.2, (r2=0.940). A significant (P<0.01) and moderate correlation was observed between protein content and ACE inhibition (r2=0.649). It can be indicated that among other useful substances of cocoa, its peptides and amino acids could contribute to its health-promoting properties. Furthermore, these bioactive substances can be exploited into functional foods or used as a source of nutraceuticals.